THE DESIGN OF TEACHING WRITING MATERIALS FOR UNIVERSITY STUDENTS: A GENRE BASED APPROACH - Agus Wismanto; Arisul Ullumudin (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2022)
This study aims to (1) describe the needs of textbooks in learning to news writing which are used as development teaching materials and design learning, (2) design textbooks and design learning that are in accordance with the analysis of student needs, (3) develop text books and design learning for news writing based on a genre process approach for students, and (4) to find out the potential influence of developing news writing text books and design learning based on the genre process approach to learning outcomes. This research is research and development. The subjects in this study were 26 students. The results of the study indicate that the news writing text book and design learning as a result of this development has a potential influence in improving students' abilities and understanding of news writing materials in university.